Pengembangan dan Efektivitas Buku Panduan Konseling Karir Ginzberg dengan Teknik Modeling untuk Memilih Studi Lanjut Siswa - I Komang Agus Ugrasena; I Ketut Dharsana; Kadek Suranata (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2022)
One of the factors that forms the basis of research is the need for guidance and counseling teachers regarding guidebooks that can be used as teaching references related to students' further studies, Andori, A. Z. (2013). The purpose of this study: (1) to know the procedures for developing guidebooks, their validity, practicality and effectiveness of guidebooks. This study used the method (R&D) using the 4D step, namely, define, design, development and dessimination which focused on class IX students of SMPN 9 Denpasar as research subjects. While the object of research is the guidebook of Ginzberg's counseling theory in giving consideration to students' further studies, Yavuz, O. (2022) Data collection techniques were carried out through questionnaires. The results of the study concluded that the results obtained from the validity test using Lawshe, Gilbert, G. E., & Prion, S. (2016) CVR and CVI showed a per-item value greater than 0 (CVR>0). Furthermore, the results of the Lashe CVI analysis obtained a score of 1. Based on the data analysis, it means that the content validity value of the guidebook product is high, meaning that it is considered feasible to be developed. These results indicate that, the guidebook Ginzberg Counseling Theory with Modeling Techniques for Selecting Students' Advanced Study Meets relevant validity. Based on the assessment of ten (10) teachers/practitioners, the practicality of this guide was found with an average result of 88%, meaning that this guidebook meets the practical criteria used by Guidance and Counseling Teachers. Based on the analysis of the t test performed, it was obtained that t = -19,896 with a smaller significance of 0.05. this means that the application of the Ginzberg Counseling Theory guidebook with Modeling Techniques Gemino, A., & Wand, Y. (2003) for Selecting Further Studies is effectively used to select student further studies and fulfills the requirements for writing a good guidebook, Dantes (2021), namely (1) High validity value, (2) Value high reliability, (3) Fulfills high practicality tests, (4) Able to adapt to the media used, (5) Fulfills the effectiveness of the contents of the manual.